PENGARUH VARIASI WAKTU PENAHANAN TEMPERATUR TERHADAP PRODUK PIROLISIS LIMBAH SERABUT SAGU (Metroxylon sp.) DENGAN ATAU TANPA KATALIS - Supeni, Yustina (Chem Info Journal, 2013)
Have been made with sago fiber waste pyrolysis hold time variation of temperature on the product with or without catalyst. Activation of natural zeolite is done by soaking 1% HF, HCl 1N (each 4 hours), washing with akuabides, and calcined. Impregnation active zeolite with a salt solution NiCl2.6H2O, calcined, oxidised and reduced. The study begins with the pyrolysis of waste sago fibers 50 grams (2.5 grams of catalyst addition on the catalytic pyrolysis) with variations detention time 0 (without detention), 5, 10, 15, 20 minute intervals 1000C to 4000C. The percentage increase in the crystallinity of the zeolite after impregnation of 2.3% but a decline in surface lus, faint flattened, and the pore volume while increasing the acidity of 0.182 mmol/g. The results showed gains weight liquid bio-oil optimum pyrolysis without catalyst that detention at 5 minutes with a weight of 23.032 grams and the pyrolysis with Ni-zeolite catalyst in a 10-minute detention with a weight of 21.292 grams. The main products of liquid between the results without the use of catalysts and catalyst have 4 short-chain hydrocarbons with the greatest abundance of acetic acid; phenol, 2-propanon,1-hydroxy, and 2-furankarboksaldehid, while appearing in the specification that the methanol pyrolysis without catalyst (detention time of 15 minutes) and 2-furanmetanol on pyrolysis catalysts (all detention time).